Ustadan Çırağa Tiroid Hastalıkları - Anuk, Turgut; Parlak, Seçil Nazife; Memiş, Ufuk; Beger, Orhan; Uçar, Hadice; Üstündağ, Hilal; Şentürk, Esra; Aydın, İlyas Halil; Öztürk, Nurinnisa; İlik, İbrahim; Yılmaz Kartal, İdeal Beraa; Binici, Serhat; et al. (2023)
-